Analysis of Medicine Procurement Planning using FIFO and FEFO Methods at West Pasaman Regional Hospital - Daulay, Ayu Sasmita; Girsang, Ermi; Ramadhani Nasution, Sri Lestari (Buletin Farmatera, 2024)
Abstract: Planning in medicine procurement is carried out because inefficiency can harm the smooth procurement of drugs for pharmaceutical service activities in the provision of overall health services, both medical, social and economic. Therefore, careful planning and medicine procurement management is needed. Stock-outs and stagnation that occur can also be influenced by drug storage methods that do not apply the First Expired First Out (FEFO) and First In First Out (FIFO) principles. This research aims to analyze medicine procurement planning using the FIFO and FEFO methods at the West Pasaman Regional Hospital using a descriptive research design through a qualitative approach. The results of this research conclude that the human resources, budget, facilities and infrastructure as well as procedures included in the input picture for drug procurement planning using the FIFO and FEFO methods at the West Pasaman District Hospital are under need, as are the human resources that have been met, the available budget and the facilities and infrastructure that has been fulfilled. However, several things must be evaluated regarding facilities and infrastructure, namely in the warehouse section, where the West Pasaman Regional Hospital still has a warehouse that is not conducive to procuring medicines.